Selective local tone mapping - Artusi, Alessandro; Akyüz, Ahmet Oǧuz; Roch, Benjamin; Michael-Grigoriou, Despina; Chrysanthou, Yiorgos L.; Chalmers, Alan G. (My University, 2013)
When preparing high dynamic range images (HDR) for display on standard monitors, it is often necessary to make a choice between global and local tone mapping. While the former is simple and efficient, it may fail to reproduce details in high contrast image regions. Although, the latter can better reproduce details in such regions, it often comes at the cost of increased complexity and computational time. In this paper, we present an algorithm that combines the best of both approaches. We perform local tone mapping only in high frequency image regions where the visibility of details can be an issue. In low frequency regions, we employ global tone mapping to save computational resources without degrading quality. Our algorithm is most suitable for tone mapping operators (TMOs) that utilize the concept of local adaptation luminances.
Keywords: Tone mapping; High dynamic range imaging; GPU; Real-time